(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Present paper is an attempt to create awareness among tenth standard students of Mira Bhayander Municipal Corporation towards ICT by using computer and internet as an effective means to actively engage them in day to day teaching learning process.The rational for selection of the topic is to update students’ knowledge with latest approach of ICT and make them aware so that they do not face much difficulty in this modern competitive world as everything is globalized revolutionary with modern new technology.The present study uses experimental method and the main objectives of present research was to develop modules for creating awareness among secondary school students, implement the module on the experimental group. The main objectives of the study was to compare the pretest and posttest mean scores of ICT awareness of experimental group, to compare the pretest and posttest mean scores of ICT awareness of control group, to compare the pretest mean scores of ICT awareness of Experimental and control group and to compare the posttest mean scores of ICT awareness of Experimental and control group. The sample consists of 100 students i.e., total sample was divided into two groups 50 students for control group and 50 students for experimental group. The data were analysed by t-test and it reveals that hypotheses 1 and 4 were significant while hypotheses 2 and 3 were non-significant.